Hip strengthening exercise dosage is not associated with clinical improvements after total hip arthroplasty – a prospective cohort study (the PHETHAS-1 study) - Merete Nørgaard Madsen; Lone Ramer Mikkelsen; Michael Skovdal Rathleff; Kristian Thorborg; Thomas Kallemose; Thomas Bandholm (BMC Musculoskeletal Disorders)
Abstract Background Postoperative rehabilitation exercise is commonly prescribed after total hip arthroplasty (THA), but its efficacy compared to no or minimal rehabilitation exercise has been questioned. Preliminary efficacy would be indicated if a dose-response relationship exists between performed exercise dose and degree of postoperative recovery. The objective was to evaluate the preliminary efficacy of home-based rehabilitation using elastic band exercise on performance-based function after THA, based on the association between performed exercise dose and change in performance-based function (gait speed) from 3 (start of intervention) to 10 weeks (end of intervention) after surgery. Methods A prospective cohort study was conducted. Following primary THA, patients were prescribed home-based rehabilitation exercise using elastic bands. Performed exercise dose (repetitions/week) was objectively measured using attached sensor technology. Primary outcome was change in gait speed (40 m fast-paced walk test). Secondary outcomes included patient-reported hip disability. In the primary analysis, a linear regression model was used. Results Ninety-four patients (39 women) with a median age of 66.5 years performed a median of 339 exercise repetitions/week (1st-3rd quartile: 209–549). Across outcomes, participants significantly improved from 3 to 10-week follow-up. The association between performed exercise dose and change in mean gait speed was 0.01 m/s [95% CI: -0.01; 0.02] per 100 repetitions. Conclusions We found no indication of preliminary efficacy of home-based rehabilitation exercise using elastic bands, as no significant and clinically relevant associations between performed exercise dose and changes in outcomes were present. Trials comparing postoperative rehabilitation exercise with no exercise early after THA are warranted. Trial registration Pre-registered: ClinicalTrials.gov (Identifier: NCT03109821, 12/04/2017).